ZAČECI ORGANIZOVANOG SPORTA U CRNOJ GORI - Dimitrije Rašović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
There are a few inscriptions,publications,proceedings and articles from history of sport and physical education in the XIX century and beginning of XX century in compa- ring to the history of theater, poetry, military science etc. This treatment probably produ- ced that the physical education and sport in the kingdom of Montenegro was the lowest investigated society activity.The special edition have had a very few in some magazine and journal in the form of articles and trough the some heroics poems. All knowledge about sport in Montenegro in that period was found in the first Montenegrian journal "Crnogorac" which was published in 1881,two years leather journal was changed na- me in to "Glas Crnogorca".In that period also was published some others journals like "Cetinjski vjesnik","Ustavnost , journal "Orlic","Luca","Knjizevni list","Dan","Ze- ta","Nova Zeta","Crnogorka","Zdravlje" I "Prosvjeta".In "Prosvjeta" was published the first inscription about gymnastics and military practices like a subject in schools